MicroRNA155 in non-small cell lung cancer: a potential therapeutic target - Wei, Xiangju; Xiong, Xianmin; Chen, Ze; Chen, Bi; Zhang, Cantang; Zhang, Wenhui (Frontiers in Oncology, 2025)
Lung cancer (LC) is the second most commonly diagnosed cancer among both men and women, and it stands as the leading cause of cancer-related mortality, characterized by high rates of morbidity and mortality. Among its subtypes, non-small cell lung cancer (NSCLC) is the most prevalent and one of the most challenging malignant tumors to treat. To date, various therapeutic approaches, including surgery, radiotherapy, and chemotherapy, have been employed in the management of lung cancer; however, due to its aggressive nature, the survival rates remain low. Consequently, exploring novel treatment strategies is of paramount importance. MicroRNAs (miRNAs), a large family of non-coding RNAs, play crucial roles in regulating several key biological processes, including cell proliferation, differentiation, inflammation, and apoptosis. Among these, microRNA155(miR-155) is one of the most conserved and versatile miRNAs, predominantly overexpressed in various diseases, including malignant tumors. This review elucidates the biological functions and roles of miR-155 in NSCLC and discusses its potential significance as a therapeutic target for future research directions and clinical applications.